Creative Skills: Flipped Classroom by Applying an Interleaving Technique for Product Design Students - Songwut Egwutvongsa (My University, 2022)
This research had the objective to compare the learning results with the creative ideas in product design work for product design student groups by using new and old teaching models. The group sampling comprised senior student groups of the Department of Design Education, King Mongkut’s Institute of Technology Ladkrabang totaling 60 people that were classified into two learning groups: 1. The group that used the teacher-centered method totaling 30 people,and 2.the integration learning group of STEM and flipped classroom totaling 30 people. The learning assessment of the creative ideas used the thinking skills test for the product design with the reliability value for Kr-20 that had a difficulty value of (p)=0.436, discrimination value of (r)=0.359, reliability value for KR-20=0.7657 or 76%, and the Cronbach's alpha coefficient that was equal to 0.7286 or 72%. In comparing the result, it was found that the effectiveness for the new teaching model emphasized the integration with multiple teaching techniques by measuring the score level values of the creative ideas that had a higher level than the original teaching model, which used the teacher-centered method. This had a statistical significance level of .05. Moreover, this showed the result of the satisfaction assessment of the students, who learned by using the integration teaching technique of STEM and a flipped classroom to be an excellent level (mean=4.47; SD=0.579), including the happiness relationship during the study (mean=4.65; S.D.=0.483), which had a statistical significance level of .05.

Received: 12 January 2022 / Accepted: 6 April 2022 / Published: 5 May 2022
Keywords: Value (mathematics); Technology-Enhanced Education Studies